Incorporating Local Resources for Developing Skill-based Education - Bhattarai, Taranath (Bhairahawa Campus Journal, 2024)
Human activities on environment and proper utilization of local resources, of course, open the door of practice and activities and ultimately lead to skill-based practical education resulting high skilled manpower easily adjustable in national and international arena and it minimizes unemployment. This study attempts to establish a connection between local resources and skill-based practical education highlighting the inclusion of local potentialities in local curriculum. Based on qualitative method, the data have been generated through PRA, classroom observation, and semi-structured interview. The collected data have been analyzed using thematic analysis under interpretative paradigm. The study has revealed the abundantly available resources or potentialities including local manpower that can be incorporated for developing skill-based outcomes in students and provides some rationale on the strategies for the development of contextual local curriculum for the development of skill-based education in study area and in general.